Studi Eksperimen Nilai Unit Horse Power Terhadap Depth of Cut Proses Pembubutan pada Material Baja Karbon Sedang - Salam, Gafar; Kadir, Abd .; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2021)
The machining process is a manufacturing process where the main process is to release or remove some of the material from a basic material which can be in the form of a shaft so that it meets the desired shape and quality. The purpose of this study was to determine the value of Unit Herse Power on the Depth of Cut turning process on medium carbon steel material. The study used medium carbon steel material in the form of a cylinder with an initial diameter of 40 mm and a length of 150 mm. The cylindrical workpiece is turned at a speed of 185 rpm and the depth of cut is varied by 1 mm, 1.5 mm and 2 mm. The results showed that the depth of pressing of the lathe has an effect on the greater the depth of feeding in the turning process, the smaller the UHP value produced. Where the Horse Power Unit for the highest feed depth is at 1 mm with a UHP value of 1.371091 and into the lowest feed there is a 2 mm feed with a UHP value of 0.685546, and through a lathe rotation of 185 rpm which is given to the workpiece very affect the magnitude of the resulting UHP value where the UHP value is the result of feeding a chisel that is installed or used on a lathe. Keywords: Lathe process, medium carbon steel, feed depth.